The 11th International Congress on Biocatalysis (biocat2024), Hamburg, Germany, 25–29 August 2024 - Bueschler, Victoria; Bubenheim, Paul; Klippel, Barbara; Malvis Romero, Ana; Ohde, Daniel; Heins, Anna-Lena; Gescher, Johannes; Rohweder, Franziska; Liese, Andreas (Catalysts, 2025)
The “11th International Congress on Biocatalysis (biocat2024)” was part of a biennial series that unites the fields of biology and chemistry, attracting researchers from the life sciences, engineering, and computer science. This international forum provides an opportunity for scientists worldwide to connect, seek collaboration for future projects, and gain insights into contemporary topics and innovative techniques. Biocat covers a range of compelling subjects and recent advancements in biocatalysis, including enzyme discovery, evolution, and applications. This congress focused on six key topics: AI and computational methods, structure–function analysis and enzyme engineering, enzymatic and whole-cell biotransformations, reaction cascades (electro-, chemo-, and photoenzymatic synergies), bioprocess engineering and the design of smart reactors, and facing climate change through sustainability and a circular bioeconomy. In 2024, we welcomed 344 expert delegates alongside 21 internal attendees, including 154 women and 1 non-binary participant, bringing the total number of participants to an impressive 365. Established researchers and emerging scientists from academia and industry delivered a total of 119 presentations, comprising 59 standard lectures, 60 lightning talks, and 195 posters. Six industry exhibitors showcased their latest products and services, providing an excellent opportunity to strengthen the connection between science and industry. Furthermore, the biocat award, recognized as one of the most prestigious honors in biotechnology, was presented for the eleventh time in the categories of “Science in Academia”, “Lifetime Achievement,” and “Industry”.